Imniunocytochemical detection of carcinoembryonic antigen in salivary gland tumors - Itoiz, María Elina; Lanfranchi, Héctor E.; Cabrini, Rómulo Luis; Domínguez, F. V. (Elsevier, 1983)
Fil: Itoiz, María Elina Comisión Nacional de Energía Atómica; Argentina